Factors related to professional commitment of nursing students: a systematic review and thematic synthesis - Hengxi Chen; Yali Chen; Ai Zheng; Xin Tan; Ling Han (BMC Medical Education)
Abstract Background To identify the factors related to nursing students’ professional commitment. Such research can assist in identifying strategies that can be used to cultivate and strengthen professional commitment among nursing students, which can ultimately help address nursing shortages and improve the overall quality of care. Methods A systematic review using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). PubMed, EMBASE, MEDLINE, CINAHL, Cochrane Library, Web of Science were searched for English-language articles from inception and July 1, 2024.Studies were systematically screened for inclusion based on predetermined eligibility criteria. The studies were quality assessed using Non-Randomized Studies (RoBANS), the JBI Critical Appraisal Checklist, the Newcastle–Ottawa Scale (NOS), Mixed-Method Appraisal Tool (MMAT), and data were analyzed using thematic analysis. A thematic synthesis was performed to identify descriptive themes across all included studies. The process involved intensive reading of the literature, followed by the extraction of qualitative data, which was organized into topically similar codes. Researchers collaborated to merge related codes into subthemes, which were then consolidated into main themes for the final report. Results A total of 1,165 studies were identified from the search, and 16 met the predetermined inclusion criteria. Three key themes emerged from the synthesis: individual factors (age, gender, region, psychological well-being, motivation, self-efficacy, career choice and individual perception), educational factors (educator impact, academic achievement, clinical experience and learning environment) and family and social factors (family influence, influence from others and social perception).Key findings indicate that age, gender, and region significantly impact professional commitment, with female students displaying greater growth post-internship. Psychological well-being is a crucial factor, with perceived stress adversely affecting commitment levels. Motivation, self-efficacy, and pre-internship commitment are pivotal in fostering long-term engagement in the profession. Additionally, involuntary career choices correlate with lower commitment, highlighting the importance of informed decision-making. Educators play a vital role, as supportive teaching practices enhance student well-being and commitment. Academic achievement and clinical experiences further influence professional dedication. Family support and social perceptions, including occupational stigma, are also crucial in shaping commitment levels. Collectively, these findings underscore the necessity of a supportive educational environment and societal perceptions to enhance nursing professional commitment. Conclusions This review identifies key factors influencing nursing students’ professional commitment, including individual, educational, family, and social influences. To enhance commitment, it is essential to foster psychological well-being, motivation, and self-efficacy within supportive educational environments. Implementing mentorship programs and addressing societal perceptions can mitigate stigma and strengthen commitment. These findings highlight the need for targeted interventions in nursing education and policy to improve workforce retention and care quality. Future research should assess the long-term impact of these strategies. Registration The protocol for the conduct of this study was registered on the International Prospective Register of Systematic Reviews (PROSPERO) with the registration number CRD42024564848.